Layered Formation and the Compounding Gap: How Religious Values Shape Akhlak Karimah in an Indonesian State Madrasah - Rts. Novi Atul Ambiya; Ely Surayya; Dewi Hasanah; Hindun Hindun; Sachrawi Hidayat (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
This study examines how religious values are implemented to form akhlak karimah (noble character) in an Indonesian state madrasah, which pedagogical and institutional strategies mediate that implementation, and which factors enable or constrain it. The study adopts a descriptive-phenomenological case design at Madrasah Aliyah Negeri 2 Batanghari, Jambi. Data were generated through semi-structured interviews with the principal, three teachers, and six students purposively selected across grade levels; three weeks of non-participant observation; and analysis of institutional documents. Two coding cycles produced descriptive and thematic categories. Trustworthiness was addressed through source and technique triangulation, member checking, and an audit trail. Implementation operated as three functionally differentiated layers: curricular integration supplied doctrinal grammar; programmatic habituation supplied disciplined repetition; and cultural embedding through the 5S practice (Smile, Greet, Salute, Polite, and Courteous) supplied relational texture. Four strategies recurred: non-negotiable habituation, modeling paired with real-time theological framing, documented pastoral oversight, and family partnership. The aspiration–behavior gap was produced not by institutional deficiency but by the compounding interaction of heterogeneous prior formation, asymmetric family engagement, and socio-digital counter-formation. The study re-specifies Uswah Hasanah as a dynamic pedagogical mechanism rather than a static institutional property, and argues that performance indicators for state madrasahs should register the conditional nature of character-formation outcomes. Differentiated pastoral pathways, realistic family-partnership redesign, and explicit engagement with the digital moral environment emerge as the most actionable institutional moves